PENGARUH PENERAPAN SAP, PEMANFAATAN TEKNOLOGI INFORMASI DAN KUALITAS SDM TERHADAP KUALITAS LAPORAN KEUANGAN PEMERINTAH DAERAH KABUPATEN PATI - Heni Risnawati; Nurani Puspa Ningrum (Universitas Muhammadiyah Kudus, 2023)
The quality of financial reports must meet the qualitative characteristics of the Government Accounting Standards. The aim of this research is to test whether SAP, utilization of information technology, quality of human resources affect the quality of financial reports. The method used is quantitative research with primary data sources through questionnaires. The research population is all employees at BPKPD Pati Regency. The sampling technique is saturated samples. For multiple regression analysis with the help of SPSS. The results partially provide evidence that SAP, Utilization of Information Technology, HR quality have a significant effect on the quality of financial reports. The results simultaneously state that Government Accounting Standards, the use of information technology and the quality of human resources have a significant effect on the quality of financial reports. Keywords: Keywords: Quality of financial reports, SAP, Utilization of information technology, HR Quality